Mysid (Crustacea: Mysidacea) Distribution in the Bolgoda Estuarine System and Lunawa Lagoon, Sri Lanka - Punchihewa, N. N.; Krishnarajah, S. R.; Vinobaba, P. (International Journal of Environment, 2017)
Mysids are one of the most abundant and important fauna in estuarine hyperbenthic communities. They form important links in estuarine food chains and play a critical role in the cycling of energy within estuarine systems. Therefore, it is important to recognize the distribution of estuarine mysids in Sri Lanka. The present study was undertaken in Bolgoda estuarine system and Lunawa lagoon, in order to find out the distribution of mysids in these brackish water systems. Reconnaissance surveys were conducted, in Bolgoda North Lake, Panadura estuary of the Bolgoda estuarine system and the Lunawa lagoon from April 2012 to February 2013. The samples were collected using a hand held dip net, during day time at low tide along an eighty meter transect at the boundary of the estuarine waters. Mesopodopsis zeylanica was the only mysid species observed from the low water areas of the lagoon along the boundary of the stream. In each collection, it was recorded, higher percentages of females than the males. Mysids were recoded only from unpolluted areas and they were absent, where Eichhornia crassipes (water hyacinth) was widespread. The findings of this analysis could be used to establish the fact that boundary condition and polluted condition are having a great effect on presence of mysids. It may be due to their specific niche requirements and specialized habitats. Accordingly, mysids serve as pollution indicator species in estuarine ecosystems. An immediate management strategy is required in protecting the Bolgoda estuarine systems from dumping household pollutants as well as other pollutants and complete elimination of the invader plants like E. crassipes, in order to protect estuarine biodiversity. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-1, Dec-Feb 2016/17, page: 23-30